(untitled) (Research, Society and Development, 2021)
COVID-19 is a pandemic disease according to the World Health Organization, responsible for causing flu manifestations and severe acute respiratory syndrome in those infected. In view of constant exposure and infection risk of health professionals, this study aimed to describe the existent scientific publications on the vulnerability this population faces in the pandemic context. It is an integrative literature review whose search was fulfilled on the 25th April of 2021, in the Virtual Library of Health. The designated descriptors to perform the search were “health personnel”, “coronavirus infections” and “risk”, associated by the boolean operator AND, leading to 545 results. Applying the filters 42 articles remained. In sequence of proper exclusions, the final sample contempled 22 articles, which were analysed and subdivided into two thematic categories. Following the analysis and search conclusion it was possible to state the major susceptibility of health professionals in the front line against COVID-19 to be infected by the disease or develop other symptoms like anxiety, psychological or sleep disorders and depression, especially as a repercussion of personal protective equipment lack.